Capricornia : a novel - Herbert, Xavier (Pymble, N.S.W : A&R Classics, 2002)
"Tells the story of Australia's north. It is a story of whites and Aborigines and Asians, of chance relationships that can form bonds for life, of dispossession, murder and betrayal"--HarperCollinsPublishers Australia.
Keywords: Aboriginal Australians -- Fiction; Northern Territory -- Fiction